The Influence of Financial Literacy, Financial Attitudes, and Lifestyle on Financial Management Behavior in The Community of Surabaya City - Vitrissia, Dian; Setyorini, Haryati (LP3M Universitas Putra Bangsa, 2024)
Financial management behavior is a person's ability to organize and control planning, budgeting, auditing, managing, controlling, raising funds, and storing financial funds on a daily basis. The purpose of this study was to examine the effect of financial literacy, financial attitudes, and lifestyle on financial management behavior in society. The number of respondents in this study was 160, with the criteria of being domiciled in the city of Surabaya and having a minimum income of IDR 4,000,000 per month. Respondent data was collected by questionnaire using judgmental (purposive) sampling and convenience sampling techniques. The analysis technique used in this study is SEM-PLS (Structural Equation Model-Partial Least Square) using the Smart PLS 3.0 program. The results of this study explain that financial literacy has no effect on financial management behavior, financial attitudes have a significant positive effect on financial management behavior, and lifestyle has no significant effect on public financial management behavior.